Associations of multiple core stability aspects with drop jump performance - Liang Guo; Meng Wu; Kaiqi Zheng; Xiaokun Gong; Zhongwei Yang; Li Li (BMC Sports Science, Medicine and Rehabilitation, 2026)
Abstract Background Drop jump performance (DJ) is essential for many ball sports. Core stability (CS) contributes to trunk control and lower-limb capacity during jump movements. The objective of this study was to investigate the relationships between multiple CS aspects and DJ performance. Methods Eighteen male university basketball players were recruited from a university. Kinematic and kinetic data of DJ were collected using infrared cameras and force plates. Five tests—sit-ups (SU), trunk extensor endurance (EE), trunk flexion-extension range of motion (TFE), dominant extremity single-leg stance time (DLS), and dominant extremity single-leg hop distance (DLH)—were used to assess core strength, endurance, flexibility, motor control, and functionality, respectively. Pearson correlation and multiple linear regression assessed the relationship between CS and DJ performance. Results DJ height (H DJ , r = 0.739, p < 0.001) and joint moment contribution rate (CR) of ankle (CRankle, r = -0.599, p = 0.009) were significantly correlated with DLH. Vertical ground reaction force (vGRF, r = 0.532, p = 0.023), peak joint moment of knee ( r = 0.494, p = 0.037), and CR of hip (CRhip, r = -0.554, p = 0.017) and knee (CRknee, r = 0.514, p = 0.029) were significantly correlated with SU. Peak joint moment of knee (PMknee, r = 0.611, p = 0.007) and ankle (PMankle, r = 0.570, p = 0.014) were significantly correlated with DLS, and PMankle was also significantly correlated with TFE ( r = -0.470, p = 0.049). Regression models were further explored to explain the H DJ (DLH, R² = 0.546, p < 0.001), vGRF (SU, R² = 0.283, p = 0.023), CRankle (DLH and TFE, R² = 0. 537, p = 0.001 and p = 0.029), CRhip (SU, R² = 0.307, p = 0.017), CRknee (SU, R² = 0.264, p = 0.029), PMknee (DLS, R² = 0.373, p = 0.007), and PMankle (DLS, R² = 0.325, p = 0.014) by the CS measurements. Conclusion Different CS-related characteristics were associated with distinct aspects of DJ performance and lower-extremity biomechanics. Functional capacity was most strongly associated with DJ height, whereas strength- and postural control-related measures were associated with specific biomechanical characteristics. These exploratory findings require confirmation in larger and interventional studies.